2004
DOI: 10.1093/geront/44.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Obesity's Effects on the Onset of Functional Impairment Among Older Adults

Abstract: Study findings support the active treatment of weight problems in older adults. Future directions for research in this area should address effective weight management interventions targeting issues related to older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 38 publications
7
89
0
3
Order By: Relevance
“…In general, previous cross-sectional and longitudinal studies have reported that older adults with a high WC (40,41) or those with an obese BMI (30 kg/m 2 or more) (5,41,42) are at a two to three times greater risk of functional impairment. The findings of the present study suggest that in older persons with HF, the effects of obesity may not influence physical function to the same degree as in older adults without this chronic illness.…”
Section: Discussionmentioning
confidence: 97%
“…In general, previous cross-sectional and longitudinal studies have reported that older adults with a high WC (40,41) or those with an obese BMI (30 kg/m 2 or more) (5,41,42) are at a two to three times greater risk of functional impairment. The findings of the present study suggest that in older persons with HF, the effects of obesity may not influence physical function to the same degree as in older adults without this chronic illness.…”
Section: Discussionmentioning
confidence: 97%
“…However, the selected equations are the most frequently used in clinical settings worldwide. The results seem to suggest the need for specific equations in obese subjects and to consider with caution the results obtained from these equations when evaluating individual capacity; ii) the different length of the walkway we used (in this study was 10 m shorter than the one used by Enright) [58] might have biased the results, although it appears very unlikely, as already commented by other authors [43], that this particular circumstance might have caused such a marked difference in the results. However, it has to be verified whether, turning around and changing direction about 25 times in a six-minute time, particularly in obese subjects where there are higher inertia and biomechanical constraints in rapid movements, would or not affect the performance; iii) a familiarization test was not performed in our sample.…”
Section: Original Articlementioning
confidence: 86%
“…Discrepancies might be due to the higher mean age in our study (10 years higher), the lower track length (20 m in our study versus 30 m), as well as the lower workload in our study. There is some evidence that track length does not appear to significantly influence the distance walked during 6MWT [43]. On the contrary, age (in particular age >60 years) may be considered one of the most important factors influencing the distance walked during the (11 studies), use of medications that could affect the exercise capacity (3 studies), use of walking aids or ortheses (4 studies), neuromuscular and ostheoarticular diseases (6 studies).…”
Section: Discussionmentioning
confidence: 99%
“…Mudanças na composição corporal durante o processo de envelhecimento são de interesse gerontológico e geriátrico e refletem fatores genéticos e ambientais tais como atividade física, nutrição, doença, bem como o processo normal de envelhecimento (Steen, 1988 Embora a literatura refira comprometimento da mobilidade e capacidade funcional do idoso em função do excesso de peso (Lacroix et al, 1993;Launer et al, 1994;Galanos et al, 1994;Zamboni et al, 1999;Apovian et al, 2002;Bannerman et al, 2002;Sternfeld et al, 2002;Jenkins, 2004), poucos estudos focaram a associação entre o peso corporal, os componentes que o constituem e o padrão anatômico da distribuição do componente adiposo com os distintos fatores que conjuntamente representam a QVRS na população idosa, destacando-se neste sentido os estudos recentes de López-García et al (2003) e de Yan et al (2004).…”
Section: 6unclassified
“…O desenvolvimento de intervenções efetivas voltadas a um significante e crescente número de idosos é vital em previnir ou postergar o desencadeamento de comprometimento funcional em idades mais avançadas, possibilitando, dessa forma, melhorar a qualidade de vida deste segmento da população em rápida expansão (Jenkins, 2004). (Bartlett, 1997).…”
Section: Ambcunclassified